AUGMENTED REALITY MAPS AS AN ALTERNATIVE HISTORY LEARNING MEDIA FOR VOCATIONAL STUDENTS - Hawiki Renalia; Blasius Suprapta (Jurnal Pendidikan Sejarah Indonesia, 2022)
This research focuses on the significance of responding to massive changes in historical learning. However, various learning issues arise, resulting in a lack of understanding of the content by students, particularly those who have not previously understood Indonesian History material well. This is due to dense learning materials and the use of ineffective learning media. As a result, students struggle to understand the material in the text-book. Based on this, learning innovations that facilitate learning Indonesian history are required. One of them is the study of prehistoric people's lives, which includes historical values, using augmented reality visual media. This media has the ability to clarify ideas, increase students' imagination and interest, and thus increase understanding of the material. Augmented reality packaged digitally can directly create interaction between students and 3D objects, facilitating information delivery. The goal of this study is to create learning media ARMAPS (Augmented Reality Maps) and evaluate their effectiveness. A 4D model was used in this study, which included: (1) definition, (2) design, (3) development, and (4) dissemination. "ARMAPS" learning media contains material pack-aged in the form of an Android application. Based on the percentage value, it is possible to conclude that the learning media "ARMAPS" is very valid and very effective for learning Indonesian history. Penelitian ini berfokus pada pentingnya merespon perubahan besar dalam pembelajaran sejarah. Namun, berbagai permasalahan pembelajaran muncul sehingga mengakibatkan kurangnya pemahaman terhadap isi materi oleh siswa, terutama yang sebelumnya belum memahami materi Sejarah Indonesia dengan baik. Hal ini disebabkan karena padatnya materi pembelajaran dan penggunaan media pembelajaran yang tidak efektif. Akibatnya, siswa kesulitan untuk memahami materi dalam buku teks. Berdasarkan hal tersebut, diperlukan inovasi pembelajaran yang memudahkan pembelajaran sejarah Indonesia. Salah satunya adalah kajian kehidupan masyarakat prasejarah yang memuat nilai-nilai sejarah melalui pemanfaatan media visual augmented reality. Media ini memiliki kemampuan untuk memperjelas gagasan, meningkatkan imajinasi dan minat siswa, sehingga meningkatkan pemahaman materi. Augmented reality yang dikemas secara digital dapat secara langsung menciptakan interaksi antara siswa dengan objek 3D, sehingga memudahkan penyampaian informasi. Penelitian ini bertujuan untuk membuat media pembelajaran ARMAPS (Augmented Reality Maps) dan mengevaluasi keefektifannya. Model 4D yang digunakan dalam penelitian ini meliputi: (1) definisi, (2) desain, (3) pengembangan, dan (4) diseminasi. Media pembelajaran “ARMAPS” berisi materi yang dikemas dalam bentuk aplikasi Android. Berdasarkan nilai persentase tersebut dapat disimpulkan bahwa media pembelajaran “ARMAPS” sangat valid dan sangat efektif untuk pembelajaran sejarah Indonesia.